2018
DOI: 10.1038/s41388-018-0308-y
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of the long noncoding RNA FOXD2-AS1 promotes carcinogenesis by epigenetically silencing EphB3 through EZH2 and LSD1, and predicts poor prognosis in gastric cancer

Abstract: Accumulating data indicate that long noncoding RNAs (lncRNAs) serve as important modulators in biological processes and are dysregulated in diverse tumors. The function of FOXD2-AS1 in gastric cancer (GC) progression and related biological mechanisms remain undefined. A comprehensive analysis identified that FOXD2-AS1 enrichment was upregulated markedly in GC and positively correlated with a large tumor size, a later pathologic stage, and a poor prognosis. Gene-set enrichment analysis (GSEA) in GEO datasets un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
109
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 113 publications
(113 citation statements)
references
References 42 publications
4
109
0
Order By: Relevance
“…In the present study, lncRNA HCG11 was shown to be downregulated in glioma tissues and cells. According to previous reports, lncRNAs are associated with the prognosis of cancer patients . In the present study, we analyzed the prognostic potential of HCG11 in glioma.…”
Section: Discussionmentioning
confidence: 90%
“…In the present study, lncRNA HCG11 was shown to be downregulated in glioma tissues and cells. According to previous reports, lncRNAs are associated with the prognosis of cancer patients . In the present study, we analyzed the prognostic potential of HCG11 in glioma.…”
Section: Discussionmentioning
confidence: 90%
“…Recent years, FOXD2-AS1 has been suggested to be overexpressed in many types of human malignancy. Similarly, Xu et al 14 indicated that FOXD2-AS1 overexpression was positively associated with tumor size, invasion depth, lymphatic metastasis, distant metastasis, and TNM stage in gastric cancer patients. Interestingly, we analyzed TCGA database which includes 460 cutaneous melanoma tissue samples and 558 normal skin tissue samples and found levels of FOXD2-AS1 expression was significantly increased in cutaneous melanoma tissues compared with normal skin tissues.…”
Section: Discussionmentioning
confidence: 84%
“…Besides, high levels of FOXD2-AS1 expression were also found in digestive system neoplasms including gastric cancer, 13,14 colorectal cancer, 15,16 and esophageal squamous cell carcinoma. Recent years, FOXD2-AS1 has been suggested to be overexpressed in many types of human malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, our results showed that nearly 20% of PGM5‐AS1 was located in the nucleus. Recent studies confirm that about one third of nuclear lncRNAs can physically interact with the PRC2 complex to epigenetically regulate gene expression, such as HOTAIR, SOX2‐OT, FOXD2‐AS1, and so on. Whether nuclear PGM5‐AS1 is able to regulate the expression of genes including PTEN through this mechanism needs further study.…”
Section: Discussionmentioning
confidence: 99%